2016
DOI: 10.17265/2328-2150/2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Carotenoid Production in Dunaliella spp. Isolated from Hypersaline Habitats in the Region of Essaouira (Morocco): Effect of NaNO3 Concentration

Abstract: Abstract:In order to determine the impact of nitrogen deficiency in medium, growth rate and carotenoids contents were followed during 15 days in two strain Dunaliella spp. (DUN2 and DUN3), isolated respectively from Azla and Idao Iaaza saltworks in the Essaouira region (Morocco). These microalgae were incubated at 25 ± 1 °C with a salinity of 35‰ and continuous light in four growth media with different concentrations of sodium nitrate (NaNO 3 ): 18.75 g/L, 2.5 g/L, 37.5 g/L and 75 g/L. Maximum of cell density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This showed that the liquid cattle rumen waste enriched with NaNO3 produced a good N/P ratio for the growth of Thalasiossira sp. Previous study showed that NaNo3 (sodium nitrate) contained high concentration of nitrate and helped the growth of Thalasiossira sp [7].…”
Section: Resultsmentioning
confidence: 99%
“…This showed that the liquid cattle rumen waste enriched with NaNO3 produced a good N/P ratio for the growth of Thalasiossira sp. Previous study showed that NaNo3 (sodium nitrate) contained high concentration of nitrate and helped the growth of Thalasiossira sp [7].…”
Section: Resultsmentioning
confidence: 99%